Adoption of dual purpose forages: Some policy implications - Lapar, Ma. Lucila; Ehui, Simeon K. (2003)
Livestock, especially ruminant, production is an important component of farming systems in upland areas of the Philippines. Moreover, since upland agriculture is becoming unsustainable because of soil erosion and productivity of crops is limited by poor soils, livestock production is a particularly valuable source of income to complement crop production. Farmers rely heavily on livestock to provide a source of savings, cash income, draft power and nutritious food. Nevertheless, scarcity and poor quality of feed are major constraints to improved livestock productivity in upland areas. Introduction of planted forages in these systems has the potential to increase substantially the quality and quantity of available forages, thus providing fodder to supplement low-quality naturally occurring forages and crop residues; concurrently, forage plants promote sustainability by improving soil quality and reducing soil erosion. Adoption of forages by smallholder farmers in the rainfed upland areas of the Philippines is conditioned by the dual-purpose role of forage plants. A number of forage species have been used as contour hedgerow species for the reduction of soil erosion. These include Gliricidia sepium, Leucaena leucocephala, Setaria spp., napier grass (Pennisetum purpureum) and vetiver grass (Vetiveria zizanioides). These species were chosen as hedgerow species because of their value as fodder for livestock, in addition to their roles in reducing soil erosion, controlling weed growth, and improving and stabilising fallow areas. A number of constraints affect the widespread adoption of forages for use as hedgerow species by smallholder farmers in the Philippine uplands. These factors include: the limited availability of seed; high mortality amongst the forage species planted; a lack of collective action; and the high initial cost of investment. Insufficient attention has been given to policy and socio-economic factors affecting adoption of forages. For example, the effects of socio-economic factors such as human capital (education, age), income and access to institutions (e.g. credit and extension) have not been studied in association with the adoption of forage species. Therefore, policy and technology options to address these issues are warranted. This paper uses an econometric approach (i.e. probit) to identify the factors affecting adoption of forages by smallholder farmers in the upland areas of the Philippines, using data from a survey conducted in 1996 by the International Rice Research Institute (IRRI). The survey examined farmers who had adopted contour hedgerow technology at 2 upland sites, Cebu, Visayas and Claveria, Mindanao, the Philippines.